IMPLEMENTASI PENDIDIKAN KARAKTER OLEH GURU DALAM MENCEGAH BULLYING DI SEKOLAH DASAR KATOLIK DON BOSKO 4 KOTA KUPANG - Mbuik, Heryon Bernard; Bouk, Ivangelista; Nitte, Yulsy Marselina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Bullying in elementary schools has become a critical educational issue because it affects students’ psychological well-being, social interaction, and academic development. Character education is increasingly recognized as an effective preventive strategy through the internalization of moral values, empathy, tolerance, discipline, and responsibility. This study aimed to analyze the implementation of character education by teachers in preventing Bullying at SDK Don Bosko 4 Kupang. The research employed a descriptive qualitative approach using a case study design. Research participants consisted of teachers, the principal, students, and parents. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that teachers implemented character education through the integration of character values in classroom learning, habituation of positive behavior, reflective discipline, collaborative learning activities, and continuous supervision of students’ social interactions. Character education contributed significantly to reducing verbal, physical, and social Bullying practices among students. The implementation also strengthened students’ empathy, mutual respect, and social responsibility while fostering a safer and more inclusive school culture. However, several challenges remained, including limited instructional time, insufficient teacher training regarding anti-Bullying strategies, and low parental involvement in reinforcing character values at home. The study concludes that consistent and collaborative implementation of character education can serve as an effective preventive framework for reducing Bullying behavior in elementary schools.